2020
DOI: 10.1083/jcb.202002144
|View full text |Cite
|
Sign up to set email alerts
|

ER–mitochondria contacts promote mitochondrial-derived compartment biogenesis

Abstract: Mitochondria are dynamic organelles with essential roles in signaling and metabolism. We recently identified a cellular structure called the mitochondrial-derived compartment (MDC) that is generated from mitochondria in response to amino acid overabundance stress. How cells form MDCs is unclear. Here, we show that MDCs are dynamic structures that form and stably persist at sites of contact between the ER and mitochondria. MDC biogenesis requires the ER–mitochondria encounter structure (ERMES) and the conserved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…Interestingly, we observed that MDC-like structures that had been released from the mitochondrial network remained associated with the ER, suggesting a stable interaction between these two cellular compartments (Figure 4A and Figure 4 Supplement 1A). In line with this observation, we recently found that MDCs form at mitochondria-ER contact sites in yeast and remain associated with the ER over extended periods (English et al, 2020). By contrast, only about 20% of all Tomm70A-enriched domains associated with lysosomes (Figure 4B-C and Figure 4 Supplement 1B) and a very small fraction associated with EEA1-TagRFP labeled endosomes or Pex14 labeled peroxisomes (Figure 4B-C and Figure 4 Supplement 1C-D).…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…Interestingly, we observed that MDC-like structures that had been released from the mitochondrial network remained associated with the ER, suggesting a stable interaction between these two cellular compartments (Figure 4A and Figure 4 Supplement 1A). In line with this observation, we recently found that MDCs form at mitochondria-ER contact sites in yeast and remain associated with the ER over extended periods (English et al, 2020). By contrast, only about 20% of all Tomm70A-enriched domains associated with lysosomes (Figure 4B-C and Figure 4 Supplement 1B) and a very small fraction associated with EEA1-TagRFP labeled endosomes or Pex14 labeled peroxisomes (Figure 4B-C and Figure 4 Supplement 1C-D).…”
Section: Resultssupporting
confidence: 61%
“…In yeast, mitochondria are linked to the ER via the ER-mitochondria encounter structure (ERMES) (Kornmann et al, 2011, 2009) and we recently showed that ERMES and its associated GTPase Gem1 are required for MDC formation (English et al, 2020). We thus tested if the Gem1 orthologs Miro1 and Miro2 (Fransson et al, 2003) are required for formation of the Tom70A-enriched structures we identified in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations